Effectiveness of Perioperative Opioid Educational Initiatives: A Systematic Review and Meta-Analysis. (11th June 2021) - Zorrilla-Vaca, Andres; Mena, Gabriel E.; Ramirez, Pedro T.; Lee, Bradley H.; Sideris, Alexandra; Wu, Christopher L.
Abstract : BACKGROUND: Opioids are the most commonly prescribed analgesics in the United States. Current guidelines have proposed education initiatives to reduce the risk of chronic opioid consumption, yet there is lack of efficacy data on such interventions. Our study evaluates the impact of perioperative opioid education on postoperative opioid consumption patterns including opioid cessation, number of pills consumed, and opioid prescription refills. METHODS: The MEDLINE/PubMed, Embase, Cochrane Library, Scopus, and Google Scholar databases were systematically searched for randomized controlled trials (RCTs) assessing the impact of perioperative educational interventions (using either paper- or video-based instruments regarding pain management and drug-induced side effects) on postoperative opioid patterns compared to standard preoperative care among patients undergoing elective surgery. Our end points were opioid consumption (number of pills used), appropriate disposal of unused opioids, opioid cessation (defined as no use of opioids), and opioid refills within 15 days, 6 weeks, and 3 months. RESULTS: In total, 11 RCTs fulfilled the inclusion criteria, totaling 1604 patients (804 received opioid education, while 800 received standard care). Six trials followed patients for 15 days after surgery, and 5 trials followed patients up to 3 months. After 15 days, the opioid education group consumed a lower number of opioid pills than those in the control group (weighted mean difference [WMD], −3.39 pills; 95% confidence interval [CI], −6.40 to −0.37; P =.03; I 2 = 69%) with no significant difference in overall opioid cessation (odds ratio [OR], 0.25; 95% CI, 0.04–1.56; P = .14; I 2 = 83%). Likewise, perioperative opioid education did not have significant effects on opioid cessation at 6 weeks (OR, 0.69; 95% CI, 0.45–1.05; P = .10; I 2 = 0%) and 3 months (OR, 0.59; 95% CI, 0.17–2.01; P = .10; I 2 = 0%) after surgery, neither reduced the need for opioid refills at 15 days (OR, 0.57; 95% CI, 0.28–1.15; P = .12; I 2 = 20%) and 6 weeks (OR, 1.08; 95% CI, 0.59–1.98; P = .80; I 2 = 37%). There was no statistically significant difference in the rate of appropriate disposal of unused opioids between both groups (OR, 1.99; 95% CI, 0.66–6.00; P = .22; I 2 = 71%). Subgroup analysis by type of educational intervention showed a statistical reduction of opioid consumption at 15 days when implementing multimedia/audiovisual strategies (4 trials: WMD, −4.05 pills; 95% CI, −6.59 to −1.50; P = .002; I 2 = 45%), but there was no apparent decrease when using only paper-based strategies (2 trials: WMD, −2.31 pills; 95% CI, −12.21 to 7.59; P = .65; I 2 = 80%). CONCLUSIONS: Perioperative educational interventions reduced the number of opioid pills consumed at 15 days but did not demonstrate a significant effect on opioid cessation or opioid refills at 15 days, 6 weeks, and 3 months. Further randomized trials should focus on evidence-based educational interventions with strict homogeneity of material to draw a more definitive recommendation.